A Discussion on the Notion of Unutilized Spaces: The Gase of Maras in Cyprus - Iscioglu, Deniz (Ankara Haci Bayram Veli Univ, 2024)
different times in the course of history, sometimes representing an abstract structure, association with human beings. Several explanations have been put forward to explain how the construct should be of, the notional framework of unutilized spaces where people do not live in, those they have abandoned or have been forced to abandon. This study attempts to redefine the notion of space in association with spaces people no more use for the purposes of residence or production. During this time, the war-torn pieces of land and premises located in the buffer zone turned into, and still are, unutilized spaces, standing lifeless in ruins where no human activity is performed. These spaces, sometimes a village or a church or a foundation in some cases, are usually controversial spaces in grounds of political reasons can be given as an example of such a space. The study results aAnew need for conceptualization other than the ones available in the literature has subject of space can be reproduced, and continue to live on, in the minds of people as Imaginational spaces also without the control of the triad of human-state-capital.
Keywords: Spa ce; Mara & scedil; North Cyprus; Imaginational Space